CCJE: Centro de Ciências Jurídicas e Econômicas - Vieira Pereira , Vinícius; Ferreira Maia, Matheus; Santos, Luiz Carlos; Dutra de Magalhães, Marcus Vinicius; da Costa, Kelly Christiny; Catelan Puppin, Natália; Dias Ferreira, Paulo; Nascimento Silva de Souza, Thallyta; da Silva Prata, Evelyn; Bastos Depianti, Janaina; Nascimento, Marília; Maciel, Márcia; et al. (Revista Guará, 2023)
Resumos dos projetos do Centro de Ciências Jurídicas e Econômicas